Cultivation of Pleurotus ostreatus (Jacq.:Fr.) Kumm. influenced by laser irradiation - Reshetnyk, K. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
It has been studied the effect of laser irradiation on growth parameters, fruiting terms and crop capacity of Pleurotus ostreatus under solid phase cultivation on different types of substrates that include sunflower husk (SH), wheat straw (WS) and floral scales of corn ears (FSCE). According to the research carried out the best P. ostreatus mycelium growth was revealed under the cultivation on 100% FSCE, the mycelium growth on 50% FSCE was 37,7% less. The mycelium growth on 50% SH, 100% SH and 50% WS substrates was 50.5%, 50.3% and 45.0% less respectively. The least mycelium growth was recorded on 100% WS substrate. Laser irradiation nonetheless had a positive effect on the mycelium growth on the substrates under analysis. In particular, the best reaction was in response to green spectrum eradiation under the cultivation on 100% wheat straw substrate that was 71.8% better than the control. Under the cultivation on other types of substrates the mycelium growth at green spectrum eradiation increased from 23.1% to 33.7% respectively. Red and blue spectra eradiation caused only slight mycelium growth changes. Green spectrum eradiation within 10 seconds promoted the crop capacity on all the substrates from 51.5 to 80.7%, except for the substrate with SH:WS:FSCE (25:25:50%), in which the crop capacity increased the most – by 87.9%. Also 10 second green spectrum impact on the mycelium reduced the substrate fouling term and accelerated the fruiting. It has been proved that the fruiting bodies grown out of the mycelium that was under 10 second green spectrum eradiation form in greater quantity compared to non-irradiated variants. Any significant differences in fungi fruiting bodies morphology on the substrates mentioned have not been found. Thus, the research carried out allowed to distinguish the most productive substrates and the most efficient mode of P. ostreatus growth stimulation with the help of laser irradiation. The results of the research prove the expediency of laser irradiation usage while cultivating macromycete P. ostreatus.